2020
DOI: 10.1016/j.scitotenv.2020.137780
|View full text |Cite
|
Sign up to set email alerts
|

Sward composition and soil moisture conditions affect nitrous oxide emissions and soil nitrogen dynamics following urea-nitrogen application

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The higher grass proportion and N uptake appeared to depress the N 2 O emission factor, but the higher legume proportion associated positively with N 2 O-N EF. Accordingly, Bracken et al [64] reported a significant functional group identity effect on cumulative N 2 O emissions, with emissions increasing with the increasing white clover proportion and decreasing with the increasing perennial ryegrass proportion for both irrigated and non-irrigated pastures. Similarly, Niklaus et al [59] reported a significant legume effect on N 2 O emission.…”
Section: Factors That Controlled N 2 O Emission and Ef At The Site 4mentioning
confidence: 99%
“…The higher grass proportion and N uptake appeared to depress the N 2 O emission factor, but the higher legume proportion associated positively with N 2 O-N EF. Accordingly, Bracken et al [64] reported a significant functional group identity effect on cumulative N 2 O emissions, with emissions increasing with the increasing white clover proportion and decreasing with the increasing perennial ryegrass proportion for both irrigated and non-irrigated pastures. Similarly, Niklaus et al [59] reported a significant legume effect on N 2 O emission.…”
Section: Factors That Controlled N 2 O Emission and Ef At The Site 4mentioning
confidence: 99%
“…Although duplicate δ 15 N bulk measurements by CRDS & SSIM and IRMS‐B of N 2 O samples from NO 3 − conversions were not significantly different, there was quite a large mean difference between samples. It could not be determined if this was because of the 15 N enrichment of these samples from an experiment in which greater variability can be expected 32 or to the concentration of these samples far exceeding the specified operating range of the CRDS instrument which may have introduced additional measurement error. Again, this shows that future users may need to consider further sample preparation steps such as accurate dilution 15 depending on their sample analysis needs.…”
Section: Discussionmentioning
confidence: 99%
“…A second comparison was carried out between CRDS & SSIM and an IRMS instrument (Sercon 20–22 Stable Isotope Ratio Mass Spectrometer coupled with a Sercon CryoPrep‐2 and Sercon autosampler; Sercon, Crewe, UK) at lab B, herein referred to as IRMS‐B. Duplicate gas samples were used from a field experiment in which a 2% 15 N‐enriched urea fertiliser was applied 32 . In the field experiment soil samples were taken periodically after fertiliser application, and soil NO 3 − was extracted using 2 M KCl and converted to N 2 O 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The optimization and/or reduction of N fertilizer applications will reduce N fertilizer application rates, which has the potential to be compensated for through increased incorporation of legumes in grasslands and arable rotations [11,12] . Legumes can fix N biologically (e.g., clover can fix up to 80-200 kg• ha −1 • yr −1 N [13,14] ) and subsequently the requirement for fertilizer is reduced, which leads to reductions in CO2, N2O and NH3 emissions associated with fertilizer manufacture, transport and application [15] .…”
Section: Reduced Use or Optimization Of Synthetic N Application Inclu...mentioning
confidence: 99%